Інститут Президента у Французькій республіці та Україні: пошук довершеного зразка - Бадида, Андріанна; Badyda, Andrianna (Видавництво Львівської політехніки, 2025)
Стаття присвячена дослідженню правового статусу Президентів у Французькій Республіці та в Україні. Обидві держави є змішаними республіками та мають певні спіль- ні ознаки. Задля розуміння переваг та недоліків у повноваженнях глав досліджуваних держав та можливої їх оптимізації в Україні й проводиться порівняльний аналіз інсти- тутів Президента, зокрема з погляду охорони Конституції та ролі Президентів у захисті прав людини, що й становить актуальність теми дослідження. І у Французькій Респуб- ліці, і в Україні Президенти є гарантами національної незалежності, неподільності тери- торії та охорони прав людини. Метою статті є аналіз повноважень Президентів Франції та України і виявлення спільних та відмінних ознак у їхньому правовому статусі. Крім того, дослідження ролі Пре- зидентів двох держав у забезпеченні ними дотримання Конституції та захисту прав людини. Президент Франції здійснює повноваження як особисто, так і разом з Прем’єр- міністром. В Україні певні акти Президента, що передбачені Конституцією, повинні скріплюватися підписами Прем’єр-міністра. В аспекті взаємодії з гілками влади, у Франції Президент Республіки очолює уряд (Раду Міністрів) за наявності Прем’єр- міністра, а в Україні роботою Кабінету Міністрів керує Прем’єр-міністр. Як у Франції, так і в Україні Президент може звертатися до органів конституційної юрисдикції з поданнями та накладати вето на закони, що порушують права людини. Крім того, про- аналізовано специфіку надзвичайних повноважень глав держав обох країн, а також про- цедуру усунення їх з посад та виявлено відмінності. Зроблено висновки, що у Французькій Республіці Конституційна рада (орган кон- ституційної юрисдикції) не може перевіряти актиПрезидента республіки на відповідність Конституції, вона перевіряє лише законодавчі положення, тоді як в Україні Конститу- ційний Суд перевіряє на відповідність Конституції акти Президента. Виявлено відмін- ності щодо відповідальності глав держав, їхнього місця у виконавчій гілці влади та впливі на уряд зокрема.

The article is devoted to the researching of the legal status of the Presidents in the French Republic and in Ukraine, because both states are semi-presidential republics and have common features. In order to understand the advantages and disadvantages of the powers of the heads of the studied states and their possible optimization in Ukraine, a comparative analysis of the institutions of the President is conducted, including fromthe point of view of protecting the Constitution and the role of Presidents in the protection of human rights, which is the relevance of the research topic. Both in the French Republic and in Ukraine, the Presidents are guarantors of national independence, territorial indivisibility and protection of human rights. The purpose of the article is to analyze the powers of the Presidents of France and Ukraine and to identify common and different features in their legal status. In addition, the study of the role of the Presidents of the two states in ensuring their compliance with the Constitution and protection of human rights. The President of France exercises authority both personally and together with the PrimeMinister, which is discussed in the article. In Ukraine, certain acts of the President provided for by the Constitution must be signed by the PrimeMinister. In terms of interaction with branches of government, in France the President of the Republic heads the government (Council of Ministers) in the presence of the Prime Minister, and in Ukraine the work of the Cabinet ofMinisters is managed by the PrimeMinister. Both in France and in Ukraine, the President can apply to the bodies of constitutional jurisdiction with submissions and veto laws that violate human rights. In addition, the specifics of the extraordinary powers of the heads of state of both countries were analyzed, as well as the procedure for their removal from office, and differences were identified. It was concluded that in the French Republic the Constitutional Council (a body of constitutional jurisdiction) cannot check the acts of the President of the Republic for compliance with the Constitution, it only checks legislative provisions, while in Ukraine the Constitutional Court checks the acts of the President for compliance with the Constitution. Differences regarding the responsibility of heads of state, their place in the executive branch of power and influence on the government, etc., were revealed.
Institute of the President in the French republic and Ukraine: search for the perfect sample
Keywords: Президент Французької Республіки; Президент України; правовий статус Президента; повноваження Президента; охорона Конституції; захист прав людини; President of the French Republic; President of Ukraine; legal status of the President; powers of the President; protection of the Constitution; protection of human rights; 342.511.1/.5-044.2(44; 477)